Utility indifference pricing of derivatives written on industrial loss indices - Leobacher, Gunther; Ngare, Philip (North-Holland, 2016)
We consider the problem of pricing derivatives written on some industrial loss index via utility indifference pricing. The industrial loss index is modeled by a compound Poisson process and the insurer can adjust her portfolio by choosing the risk loading, which in turn determines the demand. We compute the price of a CAT (spread) option written on that index using utility indifference pricing
Keywords: (Re-)Insurance; Catastrophe derivatives; Jump process; Random thinning; Utility indifference price